Pengaruh Pajak Daerah, Retribusi Daerah, Produk Domestik Regional Bruto, dan Sisa Lebih Pembiayaan Anggaran terhadap Belanja Daerah Pemerintah Pulau Sumatera - Fadiyah Lefi Anggraini; Muhammad Husni Mubarok; Desri Yanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Regional Taxes, Regional Levies, Gross Regional Domestic Product (GRDP), and Budget Financing Surplus (SiLPA) on Regional Expenditures in provincial governments on the island of Sumatra during the period 2019–2023. This study uses a quantitative approach with a panel data regression analysis method. The data used are secondary data obtained from the Regional Government Financial Report (LKPD) and the Central Statistics Agency (BPS). The independent variables consist of Regional Taxes, Regional Levies, GRDP, and SiLPA, while the dependent variable is Regional Expenditures. The results of the study indicate that Regional Taxes have a Negative and Significant effect, Regional Levies and GRDP have a significant positive effect on Regional Expenditures, while SiLPA does not have a significant effect. Simultaneously, the four independent variables affect Regional Expenditures. This finding implies that regional governments need to optimize tax revenues and encourage regional economic growth in order to increase regional spending capacity sustainably.